2019
DOI: 10.3390/met9101102
|View full text |Cite
|
Sign up to set email alerts
|

Machinability Research on the Micro-Milling for Graphene Nano-Flakes Reinforced Aluminum Alloy

Abstract: In this paper, plain aluminum was chosen as matrix alloy and graphene reinforced aluminum alloy composites was successfully prepared via powder metallurgy approach. Micro-milling experiments were conducted to explore the effect of varying graphene nanoflakes (GNFs) content (0.5%, 1.0%, and 1.5% by weight) on the machinability of composites and their machining results were compared with that of plain aluminum. Chip morphology, milling force, and machined surface morphology were used as the machinability measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The type of reinforcements and volume fraction were observed to have influenced the chip morphology. The graphene and CNT reinforcements displayed a considerable variation in chip morphology Na et al (2019). observed that, when the graphene content increases the chip formation changes from discontinuous to continuous.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The type of reinforcements and volume fraction were observed to have influenced the chip morphology. The graphene and CNT reinforcements displayed a considerable variation in chip morphology Na et al (2019). observed that, when the graphene content increases the chip formation changes from discontinuous to continuous.…”
mentioning
confidence: 89%
“…To modify the ductility and toughness of the traditional MMCs, an innovative material called MMNCs, is produced by adding nano size reinforcing particles (Poovazhagan et al, 2013). MMNC have great demand compared to conventional MMCs in the similar application ranges wherever a lesser mass owes to decrease the requirement of power and enhanced properties (Agarwal et al, 2019;Bakshi and Agarwal, 2011;Na et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be accredited to its flaky nature that has inherited the particle movement that lacked in providing better berth during lubrication. 37…”
Section: Force Components Fx Fy and Fz And Their Interaction With Inp...mentioning
confidence: 99%
“…They found that the presence of the GNPs in Mg-nanocomposite reduces the friction between the cutting tool and nanocomposite due to the lubricant effect of graphene resulting in decreasing cutting force. Na et al [ 26 ] performed the micromachining of the graphene nano-flakes (GNF) reinforced aluminum nanocomposite. The effect of feed rate and GNF contents on milled surface morphology, force component, and chip formation were investigated.…”
Section: Introductionmentioning
confidence: 99%